Challenges and Solutions in Managing Human Resources During Mergers and Acquisitions - Tukuboya, Fahrizal; Ibrahim, Muhdi B. Hi; Irawan, Andri (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2024)
This study explores the critical challenges and strategic solutions for managing human resources (HR) during mergers and acquisitions (M&As). It focuses on critical areas such as cultural integration, talent retention, harmonization of HR policies, and the use of technology in HR processes. The research employs a qualitative approach, using semi-structured interviews with senior HR managers, M&A consultants, and employees who have experienced M&As firsthand. Thematic analysis is utilized to identify and interpret patterns within the data, providing a comprehensive understanding of HR dynamics during M&As. The study identifies several key challenges: cultural integration, talent retention, harmonization of HR policies, and leveraging technology. Cultural integration is critical, with leaders needing to foster trust and collaboration. Effective talent retention strategies, including clear communication and personalized support, are essential for stability. Harmonizing HR policies requires a systematic approach and early involvement of HR professionals. Technology, such as HR information systems and digital onboarding programs, is crucial in streamlining processes and enhancing employee experience. These findings align with existing theoretical frameworks and provide actionable insights for successful HR integration. The research contributes to academic knowledge by enhancing understanding of HR management during M&As and offers practical guidelines for organizations to improve their integration processes. It highlights the importance of leadership, communication, and strategic alignment in achieving successful M&A outcomes. Future research should expand to different industries and explore long-term impacts and emerging technologies in HR integration.